The death of affirmative action? : racialized framing and the fight against racial preference in college admissions - Carter, J. Scott (Sociology teacher); Lippard, Cameron D. (Sociology of diversity., 2020)
Affirmative action in college admissions has been a polarizing policy since its inception, decried by some as unfairly biased and supported by others as a necessary corrective to institutionalized inequality. In recent years, the protected status of affirmative action has become uncertain, as legal challenges chip away at its foundations. This book looks through a sociological lens at both the history of affirmative action and its increasingly tenuous future. J. Scott Carter and Cameron D. Lippard first survey how and why so-called "colorblind" rhetoric was originally used to frame affirmative action and promote a political ideology. The authors then provide detailed examinations of a host of recent Supreme Court cases that have sought to threaten or undermine it. Carter and Lippard analyze why the arguments of these challengers have successfully influenced widespread changes in attitude toward affirmative action, concluding that the discourse and arguments over these policies are yet more unfortunate manifestations of the quest to preserve the racial status quo in the United States